Handbook of magnetic materials. - Buschow, K. H. J. (Handbook of Magnetic Materials., 2015)
Handbook of Magnetic Materials covers the expansion of magnetism over the last few decades and its applications in research, notably the magnetism of several classes of novel materials that share with truly ferromagnetic materials the presence of magnetic moments. Volume 24 of the Handbook of Magnetic Materials, much like the preceding volumes, has a dual purpose. With contributions from leading authorities in the field, it includes a variety of self-contained introductions to a given area in the field of magnetism without requiring recourse to the published literature. The book is an ideal reference for scientists active in magnetism research, providing readers with novel trends and achievements in magnetism. Each article contains an extensive description given in graphical, as well as, tabular form, with much emphasis placed on the discussion of the experimental material within the framework of physics, chemistry, and material science.